Flow-cytometry applications in plant breeding - Ciprian-Salcedo, Gean Carlo (2020)
Population growth, climate change and global warming are the great challenges facing agriculture in the 21st century. Therefore, it is necessary to increase the efficiency of selection of new varieties in plant breeding programs. In this regard, flow cytometry has proven to be a very powerful tool to speed-up selection processes in plant breeding because of its versatility and capacity to evaluate large populations.